Role of seed age in screening for salt tolerance of sunflower at germination: Role of seed age in screening for salt tolerance of sunflower at germination - LAKSHMI PRAYAGA; P LAKSHMAMMA; C SARADA (Journal of Oilseeds Research, 2020)
Three sunflower hybrid seeds of known age (3, 2 and 1 month old) seeds of DRSH-1, KBSH-44, CO-2 respectively were tested for salt tolerance by conducting germination studies in 200, 250, 300, 350 mM NaCl at monthly intervals. Results differed when seeds of same age were compared with seeds of mixed age. Therefore, for valid comparisons, the seeds should essentially be of same age.